Role of the herbicide atrazine in the development of non-Hodgkin's lymphoma. - Hoar Zahm, Shelia; Weisenburger, Dennis D.; Cantor, Kenneth P.; Holmes, F. F.; Blair, Aaron (Scandinavian Journal of Work, Environment & Health, 1993)
Atrazine is the most commonly used herbicide in the United States and is a wide-spread groundwater contaminant in the Midwest. The role of atrazine in the development of human non-Hodgkin's lymphoma (NHL) was investigated in three case-referent studies conducted in four midwestern states in the United States. A total of 993 white men with NHL and 2918 population-based referents were interviewed concerning their agricultural practices. When the results of the three studies were combined, atrazine use was associated with an odds ratio of 1.4 [95% confidence interval (95% CI) 1.1-1.8, 130 cases, 249 referents) for NHL. However, adjustments for the use of 2,4-dichlorophenoxyacetic acid and organophosphate insecticides reduced the apparent association between NHL and atrazine in all but one state and reduced the associations for the long-term and frequent users in Nebraska. Detailed analyses suggested that there was little or no increase in the risk of NHL attributable to the agricultural use of atrazine.
Keywords: agriculture; atrazine; cancer; case-referent study; epidemiology; herbicide; herbicide atrazine; non-Hodgkin’s lymphoma; occupation; triazine